Al-Ikhshid's Strategy and Leadership Style - Apipudin Apipudin (Eduvest - Journal of Universal Studies, 2022)
Al-Ikhshid is a leader who has various abilities and successes. The reign of al-Ikhshid was one of calm for the Ikhshidid dynasty. In solving problems, Al-Ikhshid used more peaceful means. Lobbying and negotiation techniques are mostly used by al-Ikhshid in achieving his goals. Both of these techniques apply a lot of persuasion. This paper aims to explain how lobbying and negotiation techniques are used by al-Ikhshid in his strategy and how al-Ikhshid's leadership style is. Through the secondary analysis method, this paper will discuss the strategies and leadership styles applied by al-Ikhshid to achieve and maintain his power. Al-Ikhshid used many lobbying techniques by establishing relationships with various powerful parties. In addition, he also applies negotiation techniques by making peace agreements. During his time as a leader, al-Ikhshid applied the benevolent autocratic leadership style which is one of the effective leadership styles. Lobbying and negotiation techniques as well as this benevolent autocratic leadership style are some of the things that are the keys to al-Ikhshid's success.